Tooth resorptions are not hereditary - Alberto Consolaro; Débora de Almeida Bianco (Dental Press Journal of Orthodontics)
ABSTRACT Root resorptions caused by orthodontic movement are not supported by consistent scientific evidence that correlate them with heredity, individual predisposition and genetic or familial susceptibility. Current studies are undermined by methodological and interpretative errors, especially regarding the diagnosis and measurements of root resorption from orthopantomographs and cephalograms. Samples are heterogeneous insofar as they comprise different clinical operators, varied types of planning, and in insufficient number, in view of the prevalence of tooth resorptions in the population. Nearly all biological events are coded and managed through genes, but this does not mean tooth resorptions are inherited, which can be demonstrated in heredograms and other methods of family studies. In orthodontic root resorption, one cannot possibly determine percentages of how much would be due to heredity or genetics, environmental factors and unknown factors. There is no need to lay the blame of tooth resorptions on events taking place outside the orthodontic realm since in the vast majority of cases, resorptions are not iatrogenic. In orthodontic practice, when all teeth are analyzed and planned using periapical radiography or computerized tomography, and when considering all predictive factors, tooth resorptions are not iatrogenic in nature and should be considered as one of the clinical events inherent in the treatment applied.